Transplant surgeons' perspective on antimicrobial stewardship: Experience with TransQIP. Issue 5 (18th October 2022) - Shwaartz, Chaya; Reichman, Trevor W.
Abstract: Antimicrobial stewardship programs (ASPs) have been shown to reduce the rates of antimicrobial resistance and improve morbidity and mortality in surgical patients. ASPs have largely been underutilized in solid organ transplant programs, and the current state of ASPs in transplantation is reviewed. Continued implementation of ASPs would likely significantly benefit transplant patients. Furthermore, coupling ASPs with robust programmatic metrics (such as transplant‐specific NSQIP) will hopefully lead to improved outcomes including morbidity and mortality of solid organ transplant recipients.